Environmental degradation and food security in Somalia - Bile Abdisalan Nor; Yusniliyana Yusof (Discover Sustainability)
Abstract Somalia grapples with significant land degradation due to soil erosion, deforestation, and overgrazing. These environmental stressors diminish agricultural productivity, further exacerbating food insecurity among the population. This study examines the impact of environmental degradation on food security in Somalia. The autoregressive distributed lag (ARDL) model was utilized with annual time-series data from 1990 to 2019. The empirical results show significant negative impacts of environmental degradation and gross domestic product (GDP) on food security, persisting in the short and long terms. However, population growth was found to have an insignificant effect on food security. Notably, while agricultural land expansion exhibits a negative effect in the short term, it emerges as a positive contributor to food security in the long term, highlighting its pivotal role in bolstering production capacity. The study suggests policy reform to prioritise initiatives for sustainable land management, focusing on reforestation, soil conservation, and watershed management. These practices are critical for mitigating environmental degradation, preserving natural resources, and enhancing the resilience of agricultural systems to climate change.